(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2025)
The article highlights the results of three years of research on the complex effect of the predecessors and new hybrids of grain sorghum Milo W and Brigga on grain yield and comparative assessment of the content of basic nutrients in grain, cereals and flour. Statement of the problem. One of the determining criteria for obtaining high yields of grain sorghum is compliance with and timely implementation of technological measures, one of which is its placement on the best predecessors, as well as the selection of hybrids with high genetic yield potential and increased adaptability to adverse abiotic factors of the growing zone. Sorghum grain is mainly used for animal feed due to its high digestibility, but its potential as an ingredient in the human diet is not yet fully understood. Today, more than ever, consumers aredemanding products that provide optimal health benefits. Materials and methods of the research.The hybrids of the French selection Brigga and the American selection Milo W were used in the research, which have a number of important features such as drought and cold resistance, high adaptability and genetic resistance to certain aphid species, resistance to lodging and shattering. The grain of the hybrids under study was grown during 2019-2021 in the Eastern Forest-Steppe at SD-Agro LLC, Izyum district, Kharkiv region. The soil of the experiment is typical chernozem with a deep humus profile, contains 5.0-6.0% humus, has good physical properties, an increased content of mobile forms of NPK and, in general, high biological activity. The growing seasons of 2019 and 2020 can be described as dry, while 2021 was quite wet. The amount of precipitation by month varied significantly. Laboratory studies were carried out at the Institute of Bioenergy Crops and Sugar Beet of the National Academy of Agrarian Sciences. Sorghum grain was processed into whole grain cereals and flour and the main composition of nutrients was determined. The mass fraction of protein substances was determined by the Kjeldahl method, fat content by the Soxhlet method, starch content by the Evers method, and sugar content by the iodometric method. The biochemical composition of the grain (starch, protein, dietary fibre, fat, ash, glucose) was determined by infrared spectroscopy according to DSTU 4117:2007 using Infratek 1241. The content of vitamins and amino acids was determined by liquid chromatography using a Chromos301 analyser. Results of the study. In order to maximise the potential of any sorghum hybrid, it is necessary to study the feasibility of growing it under different predecessors using recommended technologies in the relevant agroclimatic zone. In our studies, in all years, the best predecessor was winter wheat, which provided the highest yield of the Brigga hybrid - 7.01 t/ha, and the Milo W hybrid - 6.16 t/ha. In the French-bred Brigga hybrid, the amount of proteins was significantly lower and ranged from 8.70 g after sunflower to 9.81 g after winter wheat. As for the amount of fat in sorghum grain, the same pattern was observed, the highest amount of fat in the Brigga hybrid was observed after winter wheat. Worse predecessors such as sorghum for grain and sunflower reduced the amount of fat to 2.06 and 3.14 g, and with the best predecessor the amount of fat was 2.64 and 3.64 g. The Milo W hybrid had a significantly higher amount of proteins and fats in sorghum grain under different predecessors than the Brigga hybrid. The amount of dietary fibre in the Milo W hybrid averaged 6.39 mg, Brigga - 4.64 mg. The highest values of these nutrients were observed when sorghum was grown under winter wheat as a predecessor. With other predecessors, there was a tendency to reduce the content of protein, fat and carbohydrates. In sorghum grain, vitamin B2 was significantly less than vitamin B1. Thus, in the grain of the Milo W hybrid, riboflavin was 0.15 mg/100 g, and in the Brigga hybrid, 0.13 mg/100 g, while in cereals and flour, the amount of vitamin B2 in both hybrids decreased almost twice. Conclusion. The conducted three-year studies show that the French hybrid Brigga had a significantly higher yield than the American hybrid Milo W in the conditions of the Eastern Forest-Steppe of Ukraine. The average yield was 7.01 t/ha for the Brigga hybrid and 6.16 t/ha for the Milo W hybrid. During the years of research, the American hybrid Milo W stood out among the studied hybrids in terms of the content of proteins, fats and carbohydrates. Among the studied hybrids, the American hybrid Milo W had the highest content of these vitamins - 0.36, 0.56 and 0.34 mg/100 g, respectively. The tendency to decrease the content of B vitamins in cereals and flour was preserved in both hybrids. According to the results of the research, it was found that the content of vitamin PP is the highest in the grain of the American-bred hybrid Milo W (6.04 mg), and in the French-bred hybrid Brigga (4.97 mg). In cereals and flour, the content of this nutrient decreased in both hybrids by 0.5 and 3% in cereals and by 3 and 4.7% in flour. The grain of the American-bred Milo W hybrid had a vitamin E content of 0.52 mg/100 g, while the lower content of this vitamin was found in the grain of the French hybrid Brigga - 0.48 mg/100 g. During grain processing into cereals and flour, the amount of this nutrient decreased in both hybrids.